Continuity with the Past and Uncertainty for the Future - Reintoft Christensen, Henrik (Temenos, 2019)
The article examines the newspaper constructions of religion in Danish newspapers in a quantitative longitudinal analysis from 1750 to 2000 and a more qualitative analysis of recent news production from the last forty years. For the longitudinal part, the database of the digitization of Danish newspapers project is used. Using the available tools for quantitative data analysis, the article shows that the category of religion and world religions has been visible in Danish newspapers since 1750. The coverage of world religions is often related to thecoverage of international news. Overall, the article documents a remarkable continuity of the presence of religion. Examining the morerecent material qualitatively, the article shows that although many religions have been historically visible in the news, they have most recently become more frequent in the debate sections than in the news sections. It is primarily Islam that is debated. This is connected with a shift from religious diversity as part of foreign news coverage to domestic news coverage, related to changes in the surrounding Danish society. Nevertheless, the coverage of Islam also displays are markable continuity.